Environmental protection aspects of agriculture in landscape regions of Slovenia - Rejec Brancelj, Irena (Geografski zbornik, 1999)
In the paper, several environmental influences of agriculture in 19 selected Slovene landscape regions are described. The investigation focuses primarily on dispersed sources of agricultural pollution, i.e., farms. Based on results of field polls made at over 1000 farms, data was collected and examined on the caracteristics of fertlizing agricultural land, the use of plant protection agents, and inputs of nitrogen, one of the most important pollutant of soil and especially of water in agricultural regions. In the central part of the paper, the basic characteristic of these influences, the extent and level of pollution, and the regional differences within Slovenia are described.
Keywords: agrarna geografija; degradacija okolja; environmental protection; kmetije; kmetijska zemljišča; raba tal; umetna gnojila; varstvo okolja